Determination of genetic risk of cancer using the bleomycin test - Szyfter, Krzysztof; Jarmuż, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 1999)
The aim of the article is a presentation of an association between susceptibility to mutagens, chromosome instability and a risk of cancer incidence. This association is best pronounced in cancers induced by environmental carcinogens. The bleomycin test is described as a tool to study chromosome instability in relation to cancer. The recent attempts to extend an applicability of the test are also dercribed.